TRANSFORMING OF POULTRY MANURE INTO VALUE: COMMERCIAL STRATEGIES FOR COMPOSTING, BIOENERGY AND ANIMAL NUTRITION - Mojarla Raghavendar (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Poultry manure is generated in large quantities by the rapidly expanding poultry industry and poses serious environmental management challenges when disposed of without appropriate treatment. This review critically synthesizes commercial technologies for the valorization of poultry manure into compost, bio energy and value-added agricultural inputs, with emphasis on process performance, safety and applicability under Indian conditions. Aerobic composting (windrow, in-vessel and vermin composting), anaerobic digestion and thermo chemical conversion routes are comparatively evaluated based on operating parameters, pathogen reduction efficiency, nutrient conservation and scalability. Anaerobic digestion offers dual benefits of renewable biogas generation and nutrient-rich digestate production, while composting remains the most economically feasible option for decentralized farm- level manure management. Pyrolysis-derived biochar and bio-oil provide emerging opportunities for carbon sequestration and renewable fuel production, though economic and infrastructural barriers currently limit their adoption in India. The utilization of processed poultry manure in animal feed is constrained by regulatory and biosafety considerations. This review highlights major technological gaps, economic challenges and policy needs for sustainable poultry manure valorization and proposes integrated circular-economy frameworks suitable for Indian poultry production systems.